Anarchy, Efficiency, and Redistribution - Dieter Bös; Martin Kolmar (Center for Economic Studies and ifo Institute (CESifo), 2000)
The purpose of this paper is twofold. We first develop a contractarian theory of redistribution. The existence of rules of redistribution is explained without any recourse to the risk-aversion of individuals. Hence, we depart from the standard legitimization of redistribution as fundamental insurance and interpret it as stemming from a principle of reciprocity in trade. The second purpose of the paper is to develop a theory of institutions that implement optimal allocations. We depart from the assumption of an exogenous enforcement of constitutional rules. Hence, the self-enforcement of constitutional rules is crucial for the implementability of allocations. This approach implies that there is no allocative difference between constitutional and ordinary rules. What makes constitutions different from ordinary rules is their potential ability to create a focal point that conditions the expectations of individuals on a certain equilibrium strategy. Hence, constitutions help to solve coordination problems, not cooperation problems.
Keywords: 330; Anarchy; constitution; redistribution